Improving Completeness of Inpatient Medical Records in Menelik II Referral Hospital, Addis Ababa, Ethiopia - Kasu Tola; Haftom Abebe; Yemane Gebremariam; Birhanu Jikamo (Advances in Public Health)
Introduction. The incompleteness of medical records is a significant problem that affects the quality of health care services in many hospitals of Ethiopia. Improving the completeness of patient’s records is an important step towards improving the quality of healthcare. Methods. Pre- and postintervention study was conducted to assess improvement of inpatient medical record completeness in Menelik II Referral Hospital from September 2015 to April 2016. Simple random sampling technique was used. Data was collected using data extraction checklist and independent sample t-test was used to compare statistical difference that exists between pre- and postintervention outcomes at confidence interval of 95% and P value less than 0.05 was considered statistically significant. Result. The overall inpatient medical record completeness was found to be 84% after intervention. An enhancement of completeness and reporting of inpatient medical record completeness increased significantly from the baseline 73% to 84% during postintervention evaluation at P value < 0.05. Conclusion and Recommendation. The finding of this project suggests that a simple set of interventions comprising inpatient medical record format and training healthcare provider showed a significant improvement in inpatient medical record completeness. The Quality Officer and Chief Executive Officer of the study hospital are recommended to design and launch intervention programs to improve medical record completeness.